God, vertroue en twyfel: Die vroue in die konsentrasiekampe tydens die Anglo-Boereoorlog - Wyk, Ignatius W. C. Van (HTS teologiese studies, 2023)
God, trust and doubt: The women in the concentration camps of the Anglo-Boer or South African War.Many books and articles have been written on the religious concept of the Afrikaner women who suffered in and survived the concentration camps during the Second Anglo-Boer War (1899–1902) in South Africa. It seems as if nothing has been written, though, on their image and understanding of God. This article is an attempt to close the gap in the research. These women’s understanding of God was mainly shaped by the Old Testament. They saw the two Boer republics as the new people of God, elected to exist in freedom, as independent states. To them, God was the God of justice and righteousness, who will defend his chosen people from oppression. The defeat on the battlefield caused a crisis of faith among many women. The war diary of Johanna Brandt (née Van Warmelo) offers useful information about the women’s faith and the shattering of their faith. In the second part of this article, Lutheran perspectives on the God of the Bible and man-made idols are provided as a Christian alternative to the faith of our forefathers. The Psalms and the prophets are also revisited to point out the presence of God, as well as the ethical consequences of the Jewish-Christian religion.Contribution: This is probably one of the first articles written on women’s understanding of God, women who were confined to the concentration camps during the Anglo-Boer War of 1899–1902. The main emphasis falls on Johanna Brandt (née Van Warmelo), who was an assistant nurse in the Irene camp, on the outskirts of Pretoria. She formulated her and the other women’s belief in the God of justice. Their understanding of God motivated them to endure the hardships and thousands of deaths in the camps.